Resource allocation and empowerment of women in rural Bangladesh - International Food Policy Research Institute (International Food Policy Research Institute, 2000)
The brief states that the bargaining power of men and women crucially shapes the resource allocation decisions households make. Husbands and wives often use their bargaining power to express different priorities about how assets should be allocated. Understanding these differences and their effects is critical if policymakers are to improve livelihoods. Increasing the bargaining power of one gender group rather than another can mean the difference between policy failure and policy success. According to the study, a household survey covered 47 villages in three sites in Bangladesh, improving a woman’s bargaining power and access to resources will increase household expenditure on children’s education, but improving the same for a man generally will not. Increasing maternal control over household resources should improve the health of girl children. Given that women in Bangladesh face disadvantages with respect to both asset ownership and education, it is possible that the greatest impact of interventions that increase resources under women’s control will be felt by the next generation.